Kasma Iswari: Kontribusi Tokoh Perempuan Minangkabau dalam Bidang Pertanian (1956-2019) - Zakky Stany; Siti Fatimah (Jurusan Sejarah FIS UNP, 2020)
This article is a historical study that discusses the journey of life and experiences of a figure named Kasma Iswari from 1956-2019, she is a female researcher from Indonesia of Minang descent who is a contributor and Agent of change in agriculture. This research is a biographical study with the aim of the research to describe the life journey, roles and experiences of Kasma Iswari as a Minangkabau female figure in agriculture. This research uses the historical method which relies on four steps of activities namely heuristics, source criticism, interpretation, and historiography. Lots of achievements achieved by Kasma Iswari. Starting from discovering patent technology, becoming an agent of change in building a built village to be independent, then also succeeding in winning national level competitions, to winning individual awards as outstanding researchers at the national level. His most recent discovery was a health drink obtained from mangosteen rind extract with benefits as an anti-cancer agent. The discovery was patented in 2011, and has also been licensed to PT. Zena Sentosa Nirmala with the name of the product